Termografia infravermelha na detecção do estro em preás (Galea spixii Wagler, 1831) - Santos, Nayanne de Oliveira dos (Universidade Federal Rural do Semi-Árido, 2019)
The search for alternatives for rapid and non-invasive diagnosis has made infrared thermography an important ally for reproductive diagnosis in animals. In this context, the objective of this study was to evaluate the use of infrared thermography as a method of detecting estrus in preas (Galea spixii, Wagler, 1831). For this, during 20 days, 13 nonpregnant females of reproductive age were submitted to analysis with the thermographic camera and vaginal cytology. The females were captured with the aid of a liftnet to perform the thermographic pictures in the region of the vulva and the muzzle, body surface temperature measurement and collection of the vaginal mucus. The photos obtained with the thermographic camera were analyzed using FLIR Tolls® software. To perform the vaginal cytology, the mucus was collected with swab soaked in distilled water and fixed the material harvested in previously identified slides. The slides were stained with rapid panotic ® kit and dried at room temperature and subsequently read for identification of basal, parabasal, superficial and intermediate cells. At the same time, air temperature (Tar, °C), wind speed (Vv, m/s) and relative humidity (UR, %) were measured for environmental monitoring. It was possible to identify the estrus of all the females by the vaginal cytology, however, there was no difference in the thermographic profile nor in the measured temperatures of the analyzed regions in the period of the estrous cycle of the animals. Thus it was possible to conclude that with the use of infrared thermography in preas (Galea spixii, Wagler, 1831) it is not possible to identify the estrous period
Monografia
Keywords: Citologia vaginal; Roedores; Reprodução animal; Termografia infravermelha; Vaginal cytology; Rodents; Animal reproduction; Infrared thermography; CIENCIAS AGRARIAS::ZOOTECNIA